Analisis Efektivitas Transaksi Nontunai Pada Belanja Daerah Dalam Meningkatkan Good Governance Pada BPKAD Kabupaten Madiun - Suwarni Suwarni; Ika Farida Ulfa; Nur Sayidatul Muntiah (ITB AAS INDONESIA, 2023)
This research raises the theme of public sector accounting which focuses on the effectiveness of non-cash transactions in regional spending in improving good governance. The purpose of this research is to understand the process of implementing non-cash transactions in regional expenditure, the obstacles faced and analyze the effectiveness of non-cash transactions in improving good governance. This research was conducted at BPKAD Madiun Regency. This type of research uses descriptive qualitative. The data collection techniques used were observation, interviews and documentation. The data analysis method uses an interactive model (data reduction, data presentation, conclusion drawing). The results of the research and discussion explain that the implementation of non-cash transactions at BPKAD Madiun Regency has been implemented based on Presidential Instruction Number 10 of 2016 concerning action to prevent and eradicate corruption, Permendagri No. 910/1867 / SJ of 2017 concerning Implementation of Non-Cash Transactions in Regency / City Regional Governments and Madiun Regent Instruction No. 1 of 2017, its implementation began on January 01, 2018, the obstacle that often occurs is unstable network infrastructure which causes transactions to be delayed. From the implementation of non-cash transactions, it has been running effectively which can be seen from the realization of the budget which shows effective criteria so that it can improve good governance